Soba Candy Products Formulation with the Addition of the Seaweed Eucheuma cottonii - Sri Rahayu Kalaka; Femy M Sahami; Nikmawatisusanti Yusuf (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the formulation of soba candy without seaweed and the formulation of soba candy with the addition of seaweed, the level of preference for the panelists with the addition of seaweed and the quality characteristics of the selected seaweed soba candy. This research activity was carried out in the Laboratory of Testing and Guidance for the Quality of Fishery Products in Gorontalo Province which was divided into two stages. Preliminary research was carried out to determine the basic formulation without seaweed. The main study was to determine the formulation with the addition of seaweed (30%, 40% and 50% by weight of brown sugar) which was analyzed organoleptically using the hedonic test (level of preference) and hedonic quality. The data obtained were analyzed descriptively and to determine the differences between treatments using the Kruskall Wallis method, and to determine the selected / preferred product using the Bayes method. The results showed that the basic formulation (without seaweed) obtained was 100 g brown sugar with 200 ml coconut milk and a formula with additional seaweed that was 40% by weight of brown sugar. Characteristics of the hedonic quality of the selected products obtained in the form of soba candy with the addition of seaweed are soft, less tidy, delicious taste and specific types and specific smells and fresh without additional odor and the results of proximate analysis are 9.94% moisture content, 0.92% ash content, high levels of 4.24% fat, 3.68% protein content and 82.13% carbohydrate content. Keywords: Seaweed; brown sugar; coconut milk; candy; organoleptic.